Synthesis and Characterization of TiO2 thin film Electrode based Dye Sensitized Solar Cell - Yadav, Varsha; Chaudhary, Swati; Gupta, Saral Kumar; Verma, Ajay Singh (East European Journal of Physics, 2020)
Dye-Sensitized Solar Cells (DSSCs) are prominent alternative devices to conventional p-n junction silicon based solar cells because of their low fabrication cost and high power conversion efficiency, good cost/efficiency ratio. In the present work, DSSC devices were made-up with fluorine doped tin oxide (FTO) glass substrate, a TiO2 compact layer was deposited on FTO, Ruthenium(II) dye (N719), an iodide - triiodide electrolyte and a platinum (Pt) counter electrode. Photo anode with thin film layers of TiO2 and Pt counter electrode (photo-cathode) were prepared. Field emission electron microscope (FESEM) was employed to investigate the surface morphology of TiO2  layers. The DSSC device efficiency was evaluated by J-V characteristics. Fabricated devices were exhibited high power conversion efficiencies. The electrochemical impedance characteristics were analyzed by fitting the experimental results to the corresponding electrical equivalent circuit simulated data.